Factors that contribute to the impairment of quality of life in gastroparesis. Issue 8 (25th January 2021) - Parkman, Henry P.; Wilson, Laura A.; Yates, Katherine P.; Koch, Kenneth L.; Abell, Thomas L.; McCallum, Richard W.; Sarosiek, Irene; Kuo, Braden; Malik, Zubair; Schey, Ron; Shulman, Robert J.; Grover, Madhusudan; et al.
Abstract: Background: Understanding factors that impair quality of life (QOL) in gastroparesis is important for clinical management. Aims: (a) Determine QOL in patients with gastroparesis; (b) Determine factors that impair QOL. Methods: Gastroparetic patientsAQ6 underwent history and questionnaires assessing symptoms (PAGI‐SYM and Rome III), QOL (SF‐36v2 and PAGI‐QOL), depression (Beck Depression Inventory [BDI]), and anxiety (State Trait Anxiety InventoryAQ7). Key Results: 715 gastroparesis patients (256 diabetic (DG), 459 idiopathic (IG)) were evaluated. SF‐36 physical component (PC) score averaged 33.3 ± 10.5; 41% had impaired score <30. SF‐36 PC scores were similar between diabetic and idiopathic gastroparesis. Impaired SF‐36 PC associated with increased nausea/vomiting and upper abdominal pain subscores, acute onset of symptoms, higher number of comorbidities, use of narcotic pain medications, and irritable bowel syndrome (IBS). SF‐36 mental component (MC) score averaged 38.9 ± 13.0; 26% had impaired score <30. Poor SF‐36 MC associated with diabetic etiology, higher Beck depression inventory, and state anxiety scores. PAGI‐QOL score averaged 2.6 ± 1.1; 50% had a score of <2.6. Low PAGI‐QOL associated with higher fullness, bloating, and upper abdominal pain subscores, more depression and Trait anxiety, smoking cigarettes, need for nutritional support, progressively worsening symptoms and periodic exacerbations. Conclusions & Inferences: Multiple measures show poor QOL present in gastroparesis. Several areas impacted on reduced QOL: (a) Symptoms of nausea, vomiting, and abdominal pain, as well as IBS; (b) Etiology and acute onset and progressively worsening symptoms; (c) Comorbidities and psychological factors such as anxiety and depression; (d) Patient‐related factors such as smoking. Targeting the modifiable factors may improve patient outcomes in gastroparesis. Abstract : Multiple measures show poor quality of life present in gastroparesis. Several areas impacted on reduced quality of life: (1) Symptoms of nausea, vomiting, and abdominal pain, as well as IBS; (2) Etiology and acute onset and progressively worsening symptoms; (3) Comorbidities and psychological factors such as anxiety and depression; (4) Patient related factors such as smoking. Targeting the modifiable factors may improve patient outcomes in gastroparesis.